Eğitimde yapay zekâ kullanımı: Etik sorunlar ve çözümler. - TEMUR, Süleyman (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
Artificial Intelligence (AI) is defined as computer systems designed and programmed to imitate human intelligence and cognitive functions. Developments in AI technologies have brought about change and transformation in many fields. One of these areas is education. As a matter of fact, education systems are constantly renewed depending on the developments in AI technologies, and they change and develop by following these transformations. Moreover, educators, researchers and policy makers are showing great interest in this field due to the potential of AI to transform learning environments, improve teaching methodologies and personalize educational experiences. Although the use of AI in education offers many potential benefits, it also raises important ethical concerns. In this context, this article addresses ethical concerns about the use of AI in education. Survey model, one of the qualitative research methods, was used in the study. Firstly, the definition and basic features of AI are presented. Then, ethical issues arising from the use of AI in education are discussed. These issues include privacy, prejudice, discrimination, security, accountability, transparency, armament, digital divide, technology addiction and intellectual property. Finally, legal arrangements made in the ethical context for the use of AI in education are included. As a result of the research, the importance of using AI in education in a responsible and ethical manner was emphasized. In this framework, it was stated that educators, researchers and policy makers should act in a joint effort and develop AI policies in line with ethical principles.